2000
DOI: 10.1002/j.1681-4835.2000.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Learning Styles on Undergraduates’ Attitudes, Navigational Patterns, and Use of Navigational Tools in Hypermedia‐Based Learning

Abstract: This study aimed to identify undergraduates' learning style, their attitudes towards hypermedia-based learning (HBL), their navigational pattern and the navigational tools used during HBL sessions, and the differences in the above processes based on their learning styles. A questionnaire was used to collect data on their attitudes towards HBL. Kolb learning style inventory was used to determine the learning styles of the undergraduates. Observations and self-reports were used to determine navigational pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Conversely, previous studies in other disciplines, including nursing sciences (D'Amore et al 2012), education sciences (Magdalena 2015), cognitive sciences (Sam and Ling 2000) and business sciences (Budeva et al 2015;Ghaffari et al 2013;Goorha and Mohan 2009) have found that accommodation was the least displayed learning style. In these studies, undergraduate students were found to emphasise either the converging learning style or assimilating learning style.…”
Section: Discussion Of the Resultsmentioning
confidence: 82%
“…Conversely, previous studies in other disciplines, including nursing sciences (D'Amore et al 2012), education sciences (Magdalena 2015), cognitive sciences (Sam and Ling 2000) and business sciences (Budeva et al 2015;Ghaffari et al 2013;Goorha and Mohan 2009) have found that accommodation was the least displayed learning style. In these studies, undergraduate students were found to emphasise either the converging learning style or assimilating learning style.…”
Section: Discussion Of the Resultsmentioning
confidence: 82%
“…We believe that the way in which students perceive this cycle may influence their navigation (or interaction) with the interface. Researchers identified differences in navigational patterns between learners, but did not link this to instructional design [17]. The cyclic navigation tool provides learners with an inviting interface that encourages multiple entry points into the learning experience.…”
Section: Apply (A)mentioning
confidence: 90%
“…We believe that the way in which students perceive this cycle may influence their navigation (or interaction) with the interface, thereby influencing their learning behavior. Researchers identified differences in navigational patterns between learners, but did not link this to instructional design [14]. The cyclic navigation tool provides learners with an interface that encourages multiple entry points into the learning experience.…”
Section: How People Learn Onlinementioning
confidence: 91%